2021
DOI: 10.1186/s40942-021-00347-z
|View full text |Cite
|
Sign up to set email alerts
|

Early neurovascular retinal changes detected by swept-source OCT in type 2 diabetes and association with diabetic kidney disease

Abstract: Purpose To evaluate retinal thickness and capillary density in patients with type 2 diabetes (T2D) and their association with diabetic kidney disease (DKD) using swept-source optical coherence tomography (SS-OCT). Methods A cross-sectional study was conducted with T2D patients with mild or no diabetic retinopathy (DR) and nondiabetic controls. Inner retinal layer thickness was measured with SS-OCT. Retinal capillary density and the foveal avascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…18 Unlike Foo et al , who consider that retinal layers are relatively preserved in early stage DR, we observed that central CT is slightly correlated with GCL+ thickness in patients with DKD, confirming our previous results. 15 19 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18 Unlike Foo et al , who consider that retinal layers are relatively preserved in early stage DR, we observed that central CT is slightly correlated with GCL+ thickness in patients with DKD, confirming our previous results. 15 19 …”
Section: Discussionmentioning
confidence: 99%
“… 28 We have shown in previous studies using spectral domain OCT and SS-OCT that both retina and choroidal layers presented decreased thickness in early stages of DR (no or mild DR), especially in patients with some degree of kidney damage. 15 28 According to Liu et al , conflicting results about CT in diabetic eyes can be explained by different protocol designs, patient profiles, adjustment for confounding factors and different devices. 29 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations